KAPASITAS KEBIJAKAN DESA PUJON KIDUL KABUPATEN MALANG DALAM PENGEMBANGAN DESA WISATA - Mahirya, Wildhan Putra (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Policy Capacity of Pujon Kidul Village, Malang Regency In Tourism Village Development. This study examines the policy capacity of Pujon Kidul Village in developing tourism villages. The Tourism Village Policy, initiated by the Ministry of Tourism and Creative Economy, aims to develop local village potential. Pujon Kidul Village, which has achieved national and international accolades, has undergone a lengthy process involving all parties, including village institutions and the community. The study uses a descriptive qualitative method with policy capacity theory by Xun Wu et al. The results show that the policy capacity of Pujon Kidul Village is quite good at the individual, organizational, and system levels. However, optimization is needed in several aspects to face future tourism competition dynamics. This study recommends alternative policies including enhancing leadership capacity, improving village institution quality, maintaining local potential, and actively involving the local community in all tourism village development agendas.